PENERAPAN MODEL PRAKTIKUM ELEKTRONIKA DIGITAL BERBASIS LABORATORIUM VIRTUAL DI PERGURUAN TINGGI - Rudi Mulya; Diki Atmarizon (Politeknik Caltex Riau, 2021)
In this study, a virtual laboratory is used for Digital Electronics Practice courses which are carried out online. The research step begins with designing a virtual laboratory portal with Moodle E-Learning software to provide practice management services. The trial was carried out by running an online collaborative practice by applying the Breadboard Simulator and the TeamViewer application. The research subjects were 20 students of the Electrical Engineering Diploma III study program. The data collection instrument used a student perception questionnaire on the instructional aspect and a student perception questionnaire on the appearance of the learning model and ease of operation. Descriptive analysis was carried out using perception level criteria. The results showed that the virtual laboratory-based Digital System practice learning model had a positive perception of the instructor aspect, the learning model display aspect and ease of operation as well as increasing student motivation in carrying out practical activities.